Early diagnosis, treatment and follow-up of cystic echinococcosis in remote rural areas in Patagonia: impact of ultrasound training of non-specialists. - Mario Del Carpio; Carlos Hugo Mercapide; Juan Carlos Salvitti; Leonardo Uchiumi; José Sustercic; Hector Panomarenko; Jorge Moguilensky; Eduardo Herrero; Gabriel Talmon; Marcela Volpe; Daniel Araya; Guillermo Mujica; et al. (Public Library of Science (PLoS), 2012)
UNLABELLED: Cystic echinococcosis (CE) is a chronic, complex and neglected disease caused by the larval stage of Echinococcus granulosus. The effects of this neglect have a stronger impact in remote rural areas whose inhabitants have no chances of being diagnosed and treated properly without leaving their jobs and travelling long distances, sometimes taking days to reach the closest referral center. BACKGROUND: In 1980 our group set up a control program in endemic regions with CE in rural sections of Rio Negro, Argentina. Since 1997, we have used abdominopelvic ultrasound (US) as a screening method of CE in school children and determined an algorithm of treatment. OBJECTIVES: To describe the training system of general practitioners in early diagnosis and treatment of CE and to evaluate the impact of the implementation of the field program. MATERIALS AND METHODS: In 2000, to overcome the shortage of radiologists in the area, we set up a short training course on Focused Assessment with Sonography for Echinococcosis (FASE) for general practitioners with no previous experience with US. After the course, the trainees were able to carry out autonomous ultrasound surveys under the supervision of the course faculty. From 2000 to 2008, trainees carried out 22,793 ultrasound scans in children from 6 to 14 years of age, and diagnosed 87 (0.4%) new cases of CE. Forty-nine (56.4%) were treated with albendazole, 29 (33.3%) were monitored expectantly and 9 (10.3%) were treated with surgery. DISCUSSION: The introduction of a FASE course for general practitioners allowed for the screening of CE in a large population of individuals in remote endemic areas with persistent levels of transmission, thus overcoming the barrier of the great distance from tertiary care facilities. The ability of local practitioners to screen for CE using US saved the local residents costly travel time and missed work and proved to be an efficacious and least expensive intervention tool for both the community and health care system.